2011
DOI: 10.1038/emboj.2011.211
|View full text |Cite
|
Sign up to set email alerts
|

Direct reprogramming of stem cell properties in colon cancer cells by CD44

Abstract: Cancer progression is commonly segregated into processes of primary tumour growth and secondary metastasis. Recent evidence suggests that a subpopulation of cancer cells, cancer stem cells (CSCs), is responsible for tumour growth in cancer. However, the role of CSCs in cancer metastasis is unclear. In this study, we found that the C terminus of CD44 contributes to sphere formation and survival in vitro via the CD44-SRC-integrin axis. In addition, nuclear CD44/acetylated-STAT3 is required for clonal formation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
135
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(141 citation statements)
references
References 38 publications
4
135
0
2
Order By: Relevance
“…In fact, simply overexpressing certain oncogenic molecules (e.g., Nanog, CD44, Twist, hTERT, etc) is sufficient to reprogram primary non-tumorigenic cells or bulk cancer cells into stem-like cancer cells [136][137][138][139][140][141]. These latter observations [136][137][138][139][140][141] are consistent with the observations that such 'stemness' molecules are most frequently expressed in undifferentiated tumor cells. Finally, as CSCs constantly interact with their microenvironment, protumorigenic alterations in the microenvironment (e.g., in stromal cells) will likely affect CSC properties and promote plasticity in CSC progeny [142,143].…”
Section: Intrinsic and Induced Plasticity In Csc Progenysupporting
confidence: 79%
See 1 more Smart Citation
“…In fact, simply overexpressing certain oncogenic molecules (e.g., Nanog, CD44, Twist, hTERT, etc) is sufficient to reprogram primary non-tumorigenic cells or bulk cancer cells into stem-like cancer cells [136][137][138][139][140][141]. These latter observations [136][137][138][139][140][141] are consistent with the observations that such 'stemness' molecules are most frequently expressed in undifferentiated tumor cells. Finally, as CSCs constantly interact with their microenvironment, protumorigenic alterations in the microenvironment (e.g., in stromal cells) will likely affect CSC properties and promote plasticity in CSC progeny [142,143].…”
Section: Intrinsic and Induced Plasticity In Csc Progenysupporting
confidence: 79%
“…Experimental EMT and inflammatory cytokines IL-6, IL-8, TGFβ, and TNFα can all promote the manifestation of CSC phenotypes and properties [130][131][132][133][134][135]. In fact, simply overexpressing certain oncogenic molecules (e.g., Nanog, CD44, Twist, hTERT, etc) is sufficient to reprogram primary non-tumorigenic cells or bulk cancer cells into stem-like cancer cells [136][137][138][139][140][141]. These latter observations [136][137][138][139][140][141] are consistent with the observations that such 'stemness' molecules are most frequently expressed in undifferentiated tumor cells.…”
Section: Intrinsic and Induced Plasticity In Csc Progenymentioning
confidence: 99%
“…These include SNAI2, SNAI3, TCF4, ZEB1, and ZEB2, which have direct affinity for the CDH1 promoter, as well as TWIST1, FOXC2, and GSC, which regulate CDH1 expression indirectly (12). Strong inhibition on CD44 expression also supports the loss of matrix invasion (13) after STMN1 silencing, and likely prevents the direct reprogramming of colorectal cancer cells (14). These transcript changes following stable STMN1 silencing strongly indicate a reversal of EMT phenotype, especially in the metastatic E1 cell line.…”
Section: Stmn1 Silencing Reverses Metastatic and Emt Transcriptional mentioning
confidence: 99%
“…Previous work by Tammi et al (31) indicated that the association of HA with CD44 causes internalization of CD44 fragments, and some translocate to the nucleus (32) and modulate gene transcription by direct association and activation of gene promoters (33). To investigate whether such a mechanism operated in our cocultures, we probed for the localization of CD44 in MDA-MB-231 and MDA-MB-231 MSC .…”
Section: Hyaluronan-cd44 Interactions Mediate Msc-induced Lox and Twistmentioning
confidence: 99%